A PRAGMATIC ANALYSIS OF IRONY IN SHAKESPEARE’S HAMLET: AN OVERVIEW - Kadhim, Saad Badi (Academic Journal Research, 2025)
Objective: This study investigates the pragmatic foundations of irony in Shakespeare’s Hamlet, focusing on identifying the dominant strategies of irony, the mechanisms that trigger ironic meaning, and the development of an eclectic analytical model grounded in Leech’s and Rajimwale’s principles. Method: Employing a qualitative descriptive design, the study examines selected textual excerpts from Hamlet, analyzing the illocutionary force of ironic utterances through contextual, linguistic, and pragmatic cues. Results: Analysis reveals that destructive irony—particularly sarcasm, hyperbole, and litotes—appears far more frequently than constructive irony, serving Hamlet’s goals of confrontation, suspicion-verification, and social critique. Constructive mechanisms such as satire, pun, and banter occur rarely, functioning mainly to reduce social distance or subtly reform behavior. The findings show that irony in the play operates as a powerful communicative tool used to reveal deception, challenge authority, and expose moral corruption. Novelty: This research offers a synthesized pragmatic model capable of systematically identifying and interpreting ironic strategies in dramatic and narrative texts, providing a transferable analytical framework for future literary-pragmatic studies.